Literature Review : Analisis Senyawa Kimia sebagai Kandidat Obat Kanker Paru Menggunakan Metode Molecular Docking - Muhammad Naufal Nurhadi Hidayat; Munir Alinu Mulki; Nurlita Dwiputri Prihasti (Jurnal Sehat Mandiri, 2025)
Lung cancer is the leading cause of death worldwide, so the development of effective drugs is urgently needed. This study aims to identify potential chemical compounds as lung cancer drug candidates through molecular docking analysis. This study used a narrative literature review method with data collected from PubMed using specific keywords such as "Molecular docking," "Lung cancer," "Drug candidate," "Chemistry," and "Compound" for articles published between 2019 and 2024. Inclusion criteria included studies that analyzed chemical compounds as lung cancer drug candidates using molecular docking and met certain quantitative criteria. Of the initial 123 articles, 10 articles met the inclusion criteria and were analyzed further. The results showed significant interactions between several chemical compounds and lung cancer-related protein targets such as P-glycoprotein, NEK7, EGFR, VEGFR-2, and topoisomerase II, with high binding affinity. Overall, the results of this review highlight compound 762, SIQ17, and compound 7 as lead candidates with high therapeutic potential, which deserve further development through in vitro and in vivo tests to support their application in lung cancer therapy.